The Effect of Copper Ions on Colour in Extracts of Cabernet Sauvignon and Sangiovese Skins Under Wine-like Conditions - Rustioni, L. (South African Journal of Enology and Viticulture, 2016)
Pigment-metal complexes are generally not considered to play significant roles in grape and wine colour. However, to the best of my knowledge, this hypothesis has never been investigated. In this work, grape skin extracts (cultivars Sangiovese and Cabernet Sauvignon) were allowed to react with copper sulphate aqueous solutions at different concentrations. High, and toxic, copper additions produced significant absorption increases in the green spectral region (corresponding to the typical absorption band of anthocyanins). Further studies will be necessary to characterise the nature of this interaction.